TECHNOLOGIES OF TIMBER ASSORTMENTS HAULING BY TRACTOR-TRAILER TRAIN SQUADS - Smirnov, Mikhail; Andrianov, Yuri (Journal of Applied Engineering Science, 2018)
Technological variations of tractor-trailer timber hauling trains teamwork with tractor-mounted grapples (hydraulic manipulators) and without them are considered. The effective technology of timber assortments loading, transportation and unloading by tractor-trailer train squad is offered, which allows to reduce idle time of vehicles during terminal operations and in waiting.